2006
DOI: 10.1016/j.str.2006.03.008
|View full text |Cite
|
Sign up to set email alerts
|

GTP-Ras Disrupts the Intramolecular Complex of C1 and RA Domains of Nore1

Abstract: The novel Ras effector mNore1, capable of inducing apoptosis, is a multidomain protein. It comprises a C1 domain homologous to PKC and an RA domain similar to the Ras effectors AF-6 and RalGDS. Here, we determine the affinity of these two domains to the active forms of Ras and Rap1 using isothermal calorimetric titration. The interaction of Ras/Rap1-GTP with the RA domain of mNore1 is weakened significantly by direct binding of the C1 domain to the RA domain. In order to analyze this observation in atomic deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 36 publications
1
61
0
Order By: Relevance
“…3). In agreement with this, a previous comparison of the binding of the Nore1 RA domain with H-Ras and Rap1 showed an even larger, 10-fold difference (7,34). A lower dissociation rate is likely to be an important factor contributing to greater stability of RAPL-Rap2 complexes compared with RAPL-Rap1 (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…3). In agreement with this, a previous comparison of the binding of the Nore1 RA domain with H-Ras and Rap1 showed an even larger, 10-fold difference (7,34). A lower dissociation rate is likely to be an important factor contributing to greater stability of RAPL-Rap2 complexes compared with RAPL-Rap1 (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies of the Ras binding RA domain common to Nore1A and Nore1B/RAPL protein were limited to interactions with H-Ras and Rap1 (7,34). Using a combination of methodologies, we found that Rap2 has a K d value similar to that of H-Ras, whereas Rap1 binding was consistently lower (Fig.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Of particular interest is a recent investigation of binding affinities of the NORE1A, DAG and RA domains. An intramolecular complex can be formed between the RA and DAG-binding domains of NOR-E1A (Harjes et al, 2006). This interaction is disrupted by Ras-and Rap1-GTP thereby displacing the DAGbinding domain and revealing a lipid-binding interface with a high specificity for phosphatidylinositol 3-phosphate (PI3P).…”
Section: Rassf1mentioning
confidence: 99%
“…Increasing evidence shows that RA domains have a much wider spectrum of binding partners than just Ras-like small GTPases. Examples include the RA domain from the tumor suppressor Nore 1, which binds intramolecularly its C1 domain (Harjes et al, 2006); the Ras-binding domain (RBD) domain of plexin B1 receptor, which associates with Rho GTPases in an atypical way (Tong et al, 2007); and the RBD of Raf, which binds the SH2 domain of the Grb10 adaptor protein (Nantel et al, 1998). The Ste50p-RA domain has been previously shown to interact with the small GTPase Cdc42p, a member of Rho type of the Ras superfamily.…”
Section: Introductionmentioning
confidence: 99%